Visualizing the human capital management research domain: a bibliometric analysis approach / Wan Marhaini Wan Omar ...[et al.] - Wan Omar, Wan Marhaini; Hamid, Roseliza; Nik Md Salleh, Nik Sarina; Mat Zin, Sakinah (Universiti Teknologi MARA, 2021)
The research on human capital management has extensively emerged in recent years. Organizations need to know how to manage human capital effectively to boost performance. Many literature reviews have been published on the specific aspects of human capital management. However, less attention has been given to bibliometric and network analysis aspects. Hence, the purpose of this study is to visualize the research domain of human capital management by conducting a bibliometric analysis. The analysis was performed using Scopus Analyzer available in the Scopus database and VOS viewer software. A total of 1098 publications concerning human capital management were extracted from the Scopus database ranging from 2008 to 2018. Co-citation and co-word analysis were conducted to graphically illustrate the publication trend and to identify areas of current research interests. The outcome of this study may assist researchers in understanding the nature of human capital management research domain from across the world and suggest future research directions.